Intelligent transportation systems for electric vehicles - Elvas, L. B.; Ferreira, J. C. (Energies, 2021)
Electric Vehicles market penetration is increasing, transforming transportation, creating 8 synergies among energy and transportation. From initial blockers, like purchase price, range, charging time, lifetime, and safety are all battery-driven handicaps. In this context smart energy management system plays an important role, where intelligent process plays an important role. This review akes into account the special issue dedicated to this topic at the end of 2018, try to identify major work performed in the last 3 years and identify major topics for the upcoming years.